2005
DOI: 10.1002/cne.20546
|View full text |Cite
|
Sign up to set email alerts
|

Descending projections of the hamster intergeniculate leaflet: Relationship to the sleep/arousal and visuomotor systems

Abstract: The intergeniculate leaflet (IGL), homolog of the primate pregeniculate nucleus, modulates circadian rhythms. However, its extensive anatomical connections suggest that it may regulate other systems, particularly those for visuomotor function and sleep/arousal. Here, descending IGL-efferent pathways are identified with the anterograde tracer, Phaseolus vulgaris leucoagglutinin, with projections to over 50 brain stem nuclei. Projections of the ventral lateral geniculate are similar, but more limited. Many of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 71 publications
5
34
0
Order By: Relevance
“…The functional significance of these two classes of IGL neurons is unknown. Also unknown are the cell types that contribute to the widespread IGL connections with other brain regions and contribute to possible noncircadian functions of this nucleus (Mikkelsen, 1990;Moga and Moore, 1997;Vrang et al, 2003;Morin and Blanchard, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The functional significance of these two classes of IGL neurons is unknown. Also unknown are the cell types that contribute to the widespread IGL connections with other brain regions and contribute to possible noncircadian functions of this nucleus (Mikkelsen, 1990;Moga and Moore, 1997;Vrang et al, 2003;Morin and Blanchard, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In rodents, the IGL is a structure with a distinctive immunohistochemical profile and a characteristic pattern of efferents and afferents (Card and Moore, 1989;Harrington et al, 1987;Hickey and Spear, 1976;Morin and Blanchard, 2005). In rats and hamsters, the IGL can be identified as the region that divides the LGN into its dorsal and ventral parts, contains NPY-IR cells, receives bilateral retinal input (Morin et al, 1992Muscat et al, 2003;Pickard, 1985), and projects to the SCN and the contralateral IGL (Card and Moore, 1989).…”
Section: Pregeniculate Nucleus (Primate Homolog Of Igl + Vlg)mentioning
confidence: 99%
“…4A) (Vue et al, 2007). Thalamic neurons derived from pTH-R progenitors are thought to contribute to two dorsolaterally positioned thalamic nuclei, the ventrolateral geniculate nucleus (vLG) and the intergeniculate leaflet (IGL), neither of which projects axons to the cerebral cortex (Horowitz et al, 2004;Morin and Blanchard, 2005;Vue et al, 2007;Jones, 2007). We examined first the expression of thalamic progenitor markers at E12.5 and observed that genes expressed in the pTH-R domain (Nkx2.2, Gsx1, Ascl1, Tal1) were partially reduced in Shh SBE1/SBE1 embryos and almost completely downregulated in Shh SBE1/-mutants ( Fig.…”
Section: Sbe1mentioning
confidence: 99%
“…The rostral population of thalamic progenitors, pTH-R, consists of a narrow band of cells sandwiched between pTH-C and the zli. Thalamic neurons derived from pTH-R progenitors are thought to contribute to two dorsolaterally positioned thalamic nuclei with incompletely understood functions: the ventrolateral geniculate nucleus (vLG) and the intergeniculate leaflet (IGL), neither of which projects axons to the cortex (Horowitz et al, 2004;Morin and Blanchard, 2005;Vue et al, 2007;Vue et al, 2009;Jones, 2007).…”
Section: Introductionmentioning
confidence: 99%